Shrinkage of the human core microbiome and a proposal for launching microbiome biobanks. (May 2014) - Barzegari, Abolfazl; Saeedi, Nazli; Saei, Amir Ata
ABSTRACT: : The Human Microbiome Project (HMP) revealed the significance of the gut microbiome in promoting health. Disruptions in microbiome composition are associated with the pathogenesis of numerous diseases. The indigenous microflora has co-evolved with humans for millions of years and humans have preserved the inherited microbiomes through consumption of fermented foods and interactions with environmental microbes. Through modernization, traditional foods were abandoned, native food starters were substituted with industrial products, vaccines and antibiotics were used, extreme hygiene measures were taken, the rate of cesarean section increased, and breast feeding changed into formula. These factors have reduced human exposure to microbial symbionts and led to shrinkage of the core microbiome. Reduction in microbiome biodiversity can compromise the human immune system and predispose individuals to several modern diseases. This article suggests launching microbiome biobanks for archiving native microbiomes, supervising antibiotic use, probiotic design and native starter production, as well as advertising a revisit to native lifestyles.